Underwater robot coordination using a bio-inspired electrocommunication system. (1st September 2022) - Zhou, Yang; Wang, Wei; Zhang, Han; Zheng, Xingwen; Li, Liang; Wang, Chen; Xu, Gang; Xie, Guangming
Abstract: Due to the challenging communication and control systems, few underwater multi-robot coordination systems are currently developed. In nature, weakly electric fish can organize their collective activities using electrocommunication in turbid water. Inspired by this communication mechanism, we developed an artificial electrocommunication system for underwater robots in our previous work. In this study, we coordinate a group of underwater robots using this bio-inspired electrocommunication. We first design a time division multiple access (TDMA) network protocol for electrocommunication to avoid communication conflicts during multi-robot coordination. Then, we revise a distributed controller to coordinate a group of underwater robots. The distributed controller on each robot generates the required controls based on adjacent states obtained through electrocommunication. A central pattern generator (CPG) controller is designed to adjust the speed of individuals according to distributed control law. Simulations and experimental results show that a group of underwater robots is able to achieve coordination with the developed electrocommunication and control systems.